The Role of Teachers in Increasing Students' Learning Motivation in Islamic Religious Education - Muh Ibnu Sholeh; Muhammad Haris; Nur ‘Azah; Mochammad Syafiuddin Shobirin; Sahri; Hawwin Muzakki; Taufik Ismail; Himad Ali; Bambang Wahrudin (Jurnal Pendidikan Agama Islam, 2024)
Purpose - This study examines teachers' roles in enhancing students' learning motivation in Islamic Religious Education (PAI) at MAN 2 Tulungagung. It explores teaching strategies, challenges faced, and supporting factors contributing to increased motivation. Design/Methods/Approach - A qualitative approach involved observation, document analysis, and in-depth interviews with six key informants: PAI teachers, students, school principals, parents, and school psychologists. Data analysis followed qualitative procedures, including data reduction, presentation, and conclusion drawing. Findings - PAI teachers use group discussions, project-based learning, and technology integration to boost motivation. Teaching methods align with Self-Determination Theory (SDT) by linking lessons to students' daily lives. However, challenges like low student interest and time constraints persist. School support through training, resources, and parental involvement significantly aids motivation. Psychological factors influence learning outcomes, including self-confidence, social support, and material relevance. Research Implications/Limitations - This study highlights the importance of collaboration between teachers, schools, parents, and psychologists in fostering motivation. Findings are specific to MAN 2 Tulungagung and may not generalize to other contexts. Future research could examine similar factors in different settings. Originality/Value - This research provides new insights into the connection between teaching strategies, psychological factors, and stakeholder collaboration in religious education. It emphasizes integrating SDT principles with practical teaching methods and institutional support.